2023
DOI: 10.3390/ijerph20010851
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Utility of Waist Circumference Predicting Cardiorespiratory Fitness in School Children: A Cross-Sectional Study

Abstract: The early identification of modifiable risk factors and their monitoring, also within school physical education (PE) classes, are becoming indispensable in the context of public health. The aim of this study was to test whether making use of waist circumference (WC) measurements increases the possibility of predicting the results of cardiorespiratory fitness (CRF) in school-age children, as compared with body mass index (BMI) and other somatic indicators related to body fat. The cross-sectional study covered 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…As indicated in the introduction, BMI should not be the only index applied in the assessment of an individual's health. Our prior findings [45] have demonstrated that it is also worth including the measurement of WC in the examination of children and youth. This is a straightforward yet highly efficient measure of abdominal obesity whose result can also be used in calculating WHtR, commonly known and widely described in the literature.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…As indicated in the introduction, BMI should not be the only index applied in the assessment of an individual's health. Our prior findings [45] have demonstrated that it is also worth including the measurement of WC in the examination of children and youth. This is a straightforward yet highly efficient measure of abdominal obesity whose result can also be used in calculating WHtR, commonly known and widely described in the literature.…”
Section: Discussionmentioning
confidence: 98%
“…1/06/2014 and with all the required consent procured). The children who did not have the necessary consent or who did but were not present when the tests were being administered were not included in the project (whose details are available in the previous publication [45]). Within the tests, anthropometric measurements and a CRF test were performed, and data on the age and sex of the tested children were collected.…”
Section: Research Procedures and Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to tracking levels of CRF it has been suggested that having better levels of CRF are correlated with various positive health indicators such as lower levels of obesity. 6 , 10 Pereira et al 8 suggested that children with adequate body mass index (BMI) and CRF levels were less likely to develop chronic diseases and more likely to display positive health outcomes. Therefore, considering the impact of BMI and CRF on children’s developmental health, Stoner et al 9 suggested that it is vitality important to simultaneously measure these variables and potentially consider additional correlates that may influence these factors.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, considering the impact of BMI and CRF on children’s developmental health, Stoner et al 9 suggested that it is vitality important to simultaneously measure these variables and potentially consider additional correlates that may influence these factors. In clinical practice and research relating to children and adolescence populations, BMI is still the most reported measure of weight status and obesity due to its simple invasive approach, 10 but Lui et al 11 advocates that considering the use of BMI alone is limiting due to its lack of reference to body fat. More recently, Domaradzka et al 10 has suggested finding more than one simple to measure indicator which when combined with BMI will allow for a better estimation of health.…”
Section: Introductionmentioning
confidence: 99%